PENGARUH LINGKUNGAN KERJA NON FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SATIRA UTAMA SATU CABANG TANGERANG - Nurlaeli Auliya Fitriyani; Styo Budi Utomo (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the work environment and work discipline on the performance of PT Satira Utama Satu employees. This research tests it partially or simultaneously using quantitative methods, with data collection carried out using several methods including literature study, documentation and questionnaires. The techniques used in this research use descriptive statistical analysis techniques, data quality testing and simple linear regressionanalysis. As for the research results, based on the t test, it is known that the value of the Work Environment variable (X1) is 1.711 and the t table is 1.676 (Df = n-k-1) so (52-2- 1=49) So the conclusion can be drawn that Ho is rejected and Ha is accepted, namely the Work Environment variable (X1) which partially has a significant influence on employee performance (Y) at PT Satira Utama Satu. It is known that the value of the Development variable (X2) is 5.206 and the t table is 1.676 (Df = n-k-1) so (52-2-1=49) and is also supported by the t count > t table. So the conclusion can be drawn that Ho is rejected and Ha is accepted, namely that the Work Environment variable (X1) partially has a significant influence on employee performance (Y) at PT Satira Utama Satu. the calculated f value > f table, so the basis for the calculation is df = (n - k - 1) so that f table is 3.19, then we get calculated f > f table (20.401 > 3.19) with a score ρ value < Sig. 0.05, which in this study is (0.000 < 0.05), so finally H3 in the study is accepted and Ho is rejected, which in this study has a significant impact on the independent variables on employee performance at PT Satira Utama Satu. Based on quantitative multiple regression analysis, it was concluded that Y= 29,303 + 0.081 (X1) + 0.497 (X2) from the results of the multiple linear regression analysis, it was found that the Work Environment (X1) and Work Discipline (X2) variables had a linear effect on the Employee Performance variable (Y). And with the correlation coefficient R value of 0.674, it can be concluded that this value is in the range 0.60 - 0.799, so the level of relationship between the variables Work Environment (X1) Work Discipline and (X2) and Employee Performance (Y) there is a strong level of relationship. The R result is 0.674, so in this case it is concluded that the Work Environment variable (X1) and the Work Discipline variable (X2) have an effect on the Employee Performance variable (Y) by 67.42% while (100- 67.4%) = 32.6% influenced by other factors